Privacy of Electronic Arbitration in Libyan Law (Journal of Human Sciences, 2024)
The spread of electronic contracts and the resulting disputes have led to the search for a more flexible, faster and less complicated way to resolve disputes through ordinary courts. Security and privacy are essential factors to ensure the success of the electronic arbitration process and to build trust between the parties involved in the arbitration process. However, this is accompanied by legal and technical challenges that require effective regulation to protect data privacy. This research aims to shed light on electronic arbitration and its role in settling disputes, while evaluating the adequacy of legal texts in securing these processes. Using the descriptive analytical approach, the research discusses the concept of electronic arbitration and its distinction from similar means, its procedural rules, and legal and technical protection mechanisms. The study concluded that it is necessary to rely on artificial intelligence systems to support cybersecurity and develop it for the privacy of electronic arbitration in light of the absence of legislation. Libyan legislation also adopted a system of encrypting information sent to secure data circulated over the Internet, with some shortcomings in the technical details that require updating.